2014
DOI: 10.1007/s40261-014-0216-z
|View full text |Cite
|
Sign up to set email alerts
|

Negative Clinical Results from a Randomised, Double-Blind, Placebo-Controlled Trial Evaluating the Efficacy of Two Doses of Immunologically Enhanced, Grass Subcutaneous Immunotherapy Despite Dose-Dependent Immunological Response

Abstract: The inconclusive results were most probably influenced by a very low grass pollen season. Other factors such as the extent of the pre-seasonal treatment could potentially have contributed. The tolerability profile was acceptable for further development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Many conventional SCIT extracts and dosage regimens have failed to show significant improvement after the first year of treatment. 19 20 The rapid onset of 1 course of MPL-SCIT against grass is fascinating and in keeping with a recent study of allergic rhinitis. 21 The authors of that study evaluated the clinical efficacy and safety of ragweed MPL compared to a placebo using controlled ragweed pollen exposure.…”
Section: Discussionmentioning
confidence: 57%
“…Many conventional SCIT extracts and dosage regimens have failed to show significant improvement after the first year of treatment. 19 20 The rapid onset of 1 course of MPL-SCIT against grass is fascinating and in keeping with a recent study of allergic rhinitis. 21 The authors of that study evaluated the clinical efficacy and safety of ragweed MPL compared to a placebo using controlled ragweed pollen exposure.…”
Section: Discussionmentioning
confidence: 57%
“…This resulted in a shift of the sIgE:sIgG 4 ratio towards the induction of tolerance. These data, especially the induction of sIgG 4 , concur with those of previous studies investigating conventional and short‐course adjuvant‐containing SCIT and sublingual immunotherapy . The desirable immunological effects, which are similar to those of conventional long‐term SCIT treatment, elucidate the mechanisms of action of LPP.…”
Section: Discussionmentioning
confidence: 99%
“…However, unfavorable results were also reported. Kleine‐Tebbe et al did a double‐blind random clinical trial of SIT in 450 cases with allergic disorders and found no statistically significant differences in results between the active groups and the placebo group. Our studies found that although clinical symptoms of perennial allergic rhinitis were suppressed after treatment with a 6‐month SIT, symptoms relapsed 1 month after termination .…”
Section: Discussionmentioning
confidence: 99%